Anticoagulation practices associated with bleeding and thrombosis in pediatric extracorporeal membrane oxygenation; a multi-center secondary analysis. (March 2023) - Bailly, David K; Reeder, Ron W; Muszynski, Jennifer A; Meert, Kathleen L; Ankola, Ashish A; Alexander, Peta MA; Pollack, Murray M; Moler, Frank W; Berg, Robert A; Carcillo, Joseph; Newth, Christopher; Berger, John; et al.
To determine associations between anticoagulation practices and bleeding and thrombosis during pediatric extracorporeal membrane oxygenation (ECMO), we performed a secondary analysis of prospectively collected data which included 481 children (<19 years), between January 2012 and September 2014. The primary outcome was bleeding or thrombotic events. Bleeding events included a blood product transfusion >80 ml/kg on any day, pulmonary hemorrhage, or intracranial bleeding, Thrombotic events included pulmonary emboli, intracranial clot, limb ischemia, cardiac clot, and arterial cannula or entire circuit change. Bleeding occurred in 42% of patients. Five percent of subjects thrombosed, of which 89% also bled. Daily bleeding odds were independently associated with day prior activated clotting time (ACT) (OR 1.03, 95% CI= 1.00, 1.05, p =0.047) and fibrinogen levels (OR 0.90, 95% CI 0.84, 0.96, p <0.001). Thrombosis odds decreased with increased day prior heparin dose (OR 0.88, 95% CI 0.81, 0.97, p =0.006). Lower ACT values and increased fibrinogen levels may be considered to decrease the odds of bleeding. Use of this single measure, however, may not be sufficient alone to guide optimal anticoagulation practice during ECMO.